The Effects of Mother's Knowledge and Husband’s Support on Childbirth Assistance by a Traditional Birth Attendant - Sriwahyuni, Susy; Marniati; Putri , Enda Silvia; Husna, Arfah (International Journal of Psychosocial Rehabilitation, 2020)
Mother's knowledge and husband’s support are important for childbirth assistance by a shaman who has knowledge, skills, and makeshift tools to provide help to mothers and babies. The purpose of this study was to know the effect of mother's knowledge and husband’s support on childbirth assistance by a Traditional Birth Attendant (TBA). This type of research is analytic survey with a cross-sectional approach. The population and sample of all mothers who had babies in the Work Area of Beutong Ateuh Health Center, Beutong Ateuh Subdistrict, Nagan Raya District, as many as 76 maternity mothers were analyzed by univariate, bivariate and multivariate.The results of the study with the chi-square test showed that there was an effect of mother’s knowledge and husband’s support on childbirth assistance by the TBA (P.Value